2023
DOI: 10.5334/pme.16
|View full text |Cite
|
Sign up to set email alerts
|

Co-creation to Develop Interventions to Facilitate Deep Reflection for Dental Students

Abstract: Background: Deep reflective practice is important in healthcare education to allow students to explore emotions associated with the learning experience, access deeper learning and develop their personal and professional identity. Previous research demonstrated that the current methods of reflective practice using logbooks at the end of a clinical session to facilitate reflection within this setting were viewed as suboptimal by staff and student users. To address this problem co-creation, or a 'students as part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…The inclusion of children, teachers, and parents from the outset of the cocreation process proved challenging due to their availability and time constraints, which often conflicted with project funders' requirements and local service expectations, such as school complexes. These challenges align with findings in the literature [74,75], with logistics and timeline management being the most commonly cited difficulties. However, our study is among the few to employ cocreation with children on a sensitive topic such as mental health, allowing them to play an active role in designing and producing a health-related intervention [76].…”
Section: Anticipated Findingssupporting
confidence: 83%
“…The inclusion of children, teachers, and parents from the outset of the cocreation process proved challenging due to their availability and time constraints, which often conflicted with project funders' requirements and local service expectations, such as school complexes. These challenges align with findings in the literature [74,75], with logistics and timeline management being the most commonly cited difficulties. However, our study is among the few to employ cocreation with children on a sensitive topic such as mental health, allowing them to play an active role in designing and producing a health-related intervention [76].…”
Section: Anticipated Findingssupporting
confidence: 83%
“…Hence, this becomes an opportunity for transformation, and may inspire critical examination of pervasive norms [ 22 , 23 ]. Re-examination is essential within our increasingly complex modern healthcare environments, and assists in attending to concerns about sustainability of education [ 24 ]. Co-creating with students promotes critical thinking and creative skills [ 8 ], which are areas that the educational research community has identified to be of key importance for future research [ 25 ].…”
Section: Introductionmentioning
confidence: 99%